2016
DOI: 10.7860/jcdr/2016/21499.8353
|View full text |Cite
|
Sign up to set email alerts
|

MPV in Uncontrolled & Controlled Diabetics- Its Role as an Indicator of Vascular Complication

Abstract: MPV values are higher in uncontrolled DM patients when compared with controlled DM patients and a higher percentage of them develop microvascular complications like Diabetic Retinopathy suggesting that mean platelet volume could indicate and play a more important role in the detection of vascular complications of Diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…[20,23] Research is also being carried out in the diabetic population to find a correlation between increased MPV and the presence of microvascular complications with many studies suggesting a strong association between the two. [12,24] The current study is in corroboration with the same and is in agreement with the results of other researchers, [3,18,25,26] wherein there is a significantly higher MPV among the diabetic patients with microvascular complications when compared to those without the same (mean MPV in diabetics with microvascular complications -10.66±0.69 fl, mean MPV in diabetics without microvascular complications -10.09±0.69 fl, P value=0.024). This finding indicates that chronic hyperglycaemia and increased MPV may have a crucial role to play in the pathogenesis of microvascular complications associated with DM.…”
Section: Discussionsupporting
confidence: 92%
“…[20,23] Research is also being carried out in the diabetic population to find a correlation between increased MPV and the presence of microvascular complications with many studies suggesting a strong association between the two. [12,24] The current study is in corroboration with the same and is in agreement with the results of other researchers, [3,18,25,26] wherein there is a significantly higher MPV among the diabetic patients with microvascular complications when compared to those without the same (mean MPV in diabetics with microvascular complications -10.66±0.69 fl, mean MPV in diabetics without microvascular complications -10.09±0.69 fl, P value=0.024). This finding indicates that chronic hyperglycaemia and increased MPV may have a crucial role to play in the pathogenesis of microvascular complications associated with DM.…”
Section: Discussionsupporting
confidence: 92%
“…Of these 48 articles, 27 came from China [ 22 , 30 , 34 , 36 , 37 , 41 , 43–46 , 48 , 49 , 55–60 , 64 , 65 , 67 , 68 , 70–73 ], 16 from Turkey [ 21 , 23 , 29 , 31 , 35 , 38 , 40 , 42 , 47 , 50–54 , 61 , 69 ], 3 from India [ 32 , 63 , 39 ], 1 from Greece [ 62 ] and 1 from Kazakhstan [ 33 ]. Amongst these studies, 21 reported NLR (9 enrolled patients with DR, 12 enrolled patients with DN) [ 21 , 23 , 31 , 32 , 34 , 35 , 38 , 41–43 , 45 , 47 , 50–54 , 56–60 , 62 , 63 , 65 , 67–69 , 71–73 ], 33 reported the data of MPV (23 enrolled patients with DR, 10 enrolled patients with DN) [ 22 , 29 , 30 , 33 , 36–40 , 44 , 46 , 48–50 , 55 , 61 , 64 , 66 , 70 , 73 ], and 12 reported PDW (12 enrolled patients with DR, 3 enrolled patients with DN) [ 21 , 23 , …”
Section: Resultsmentioning
confidence: 99%
“…There were 23 articles with 3437 patients, which had data of MPV for DR [ 21 , 23 , 32 , 35 , 50–54 , 56–60 , 62 , 63 , 65 , 67–69 , 71–73 ]. Random-effects model was used to pool the data because of the significant heterogeneity amongst the included studies ( I 2 = 94.1; P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Mean platelet volume was found to be higher in patients with uncontrolled DM than those with controlled disease and healthy nondiabetic persons (Radha & Selvam, ).…”
Section: Introductionmentioning
confidence: 99%